FRI0611-HPR EUROPEAN PRESCRIBERS' PERSPECTIVES ON BIOSIMILARS. (2nd June 2020) - Reilly, M.; Feldman, M.
Abstract : Background: Biosimilars are highly similar, but not identical to originator biologics. In an increasingly resource-constrained environment, switching patients from originator biologics to biosimilars is a growing practice in many jurisdictions. Though automatic substitution of originator biologics with biosimilars is rare in Europe, this practice excludes physicians from decisions regarding the treatment of their patients. Objectives: As countries seek to control health costs and expand access to biologic therapies, building physician confidence in biosimilars is critical to promoting their use and reaping the cost benefits. This survey will empirically document their perspectives on biologic substitution. These findings may serve as a resource for countries in developing biosimilar policies which build physician confidence in biosimilars. Methods: The Alliance for Safe Biologic Medicines (ASBM) commissioned 15-minute web-based surveys among biologic prescribers in 6 Western European countries. Respondents must prescribe biologic medicines, must practice in France, Germany, Italy, Spain, Switzerland, or United Kingdom, must specialize in one of 10 practice areas: Dermatology, Endocrinology, Gastroenterology, Hematology Oncology, Immunology, Nephrology, Neurology, Oncology, Ophthalmology, Rheumatology. This survey is a refresh of one conducted in 2013 (n=470) available at www.safebiologics.org/surveys . Results: 579 responses were received, 14% from Rheumatologists (n=80). Biosimilar familiarity was high, increasing from 76% to 90% from the 2013 survey; with Rheumatologists the most familiar (99%). Similarly, the % of physicians who felt sole treatment decision authority was very important or critical had increased from 72% to 82%; among Rheumatologists again this figure was higher (85%). This pattern was found across many questions, for example the importance of retaining authority to prevent a substitution (a jump from 74% in 2013 to 84% in 2019 saying "very important or critical", with Rheumatologists higher than average at 90%). Rheumatologists had a higher than average comfort level prescribing biosimilars to new patients, but were the least comfortable with a third party switching their patient for non-medical reasons (e.g. cost): 49% were "very uncomfortable" compared to an average of 29% across specialties. Conclusion: European physicians have increased their familiarity with biosimilars since 2013, with Rheumatologists the practice area with greatest familiarity. After 13 years of experience with biosimilars, Europe's prescribers consider maintaining physician control of treatment decisions to be highly and increasingly important; Remain uncomfortable with switching a patient to a biosimilar for non-medical reasons; Are highly (and increasingly) uncomfortable with a non-medical substitution performed by a third party. When looking specifically at Rheumatologists, these trends are even more pronounced. Disclosure of Interests: Michael Reilly Grant/research support from: The organization of which I am executive director (ASBM) has received general grants from pharmaceutical companies., Madelaine Feldman: None declared